Method for refining additive manufacturing of magnesium alloy grains through interlayer coating of nano ZrO2 particles

By coating nano ZrO2 particles between layers during arc additive manufacturing, the magnesium alloy grains are refined, which solves the problem that magnesium alloy is prone to coarse columnar crystals and pores in arc additive manufacturing, and significantly improves the strength and elongation of the material.

CN119897556APending Publication Date: 2025-04-29WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510334540.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the process of arc additive manufacturing of magnesium alloys, magnesium alloys are prone to poor defects such as thick columnar crystals and pores, which affects the performance of the components, and it is difficult for traditional methods to form complex components.

Method used

Using the method of coating nano ZrO2 particles between layers, a magnesium alloy is deposited on the surface of the substrate on the CMT arc additive manufacturing system, and a coating containing nano ZrO2 particles is uniformly coated on the surface of each layer of magnesium alloy. After cooling, the next layer is deposited. This process is repeated until it is completed.

Benefits of technology

By refining the magnesium alloy grains and transforming the columnar crystal into equiaxed crystals, the strength and elongation of the material are significantly improved and the strong plastic synergistic performance of the magnesium alloy is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897556A_ABST
    Figure CN119897556A_ABST
Patent Text Reader

Abstract

The invention provides a method for refining additive manufacturing of magnesium alloy grains by coating nano ZrO2 particles between layers, which comprises the following steps of: treating the surface of a base plate on a CMT electric arc additive manufacturing system, outputting a welding wire, depositing a layer of magnesium alloy on the surface of the base plate, uniformly coating the surface of the deposited magnesium alloy with a coating containing the nano ZrO2 particles, and drying to obtain the magnesium alloy grains. And a next layer of magnesium alloy is deposited after a certain interlayer cooling time, and the process is repeated until deposition is completed. According to the method, the process is simple, materials are common, the preparation time is short, magnesium alloy grains are greatly refined under the condition that a large amount of time and cost are saved, and cooperative improvement of columnar crystal orientation isometric crystal transformation and material strength and plasticity is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal additive manufacturing, and in particular to a method for additive manufacturing of magnesium alloy grains by interlayer coating of nano ZrO2 particles. Background Art

[0002] Magnesium alloy has the advantages of low density, high specific strength and specific stiffness, good casting performance, good thermal conductivity, and impact resistance. It is currently the most promising lightweight metal structural material and is widely used in the fields of automobiles, aerospace, and electronic communications. However, magnesium alloy has poor plastic deformation ability at room temperature, and it is difficult to form some complex components using traditional manufacturing methods. As the industrial market's demand for high-quality magnesium alloys increases, traditional methods cannot meet the industrial field's manufacturing needs for large-sized, complex-structured magnesium alloy components.

[0003] Wire-arc additive manufacturing (WAAM) technology is an advanced free-form manufacturing technology that uses arc as a heat source and welding wire as a raw material to connect materials from 3D model data to objects layer by layer under the protection of inert gas. Its advantages such as no mold, free forming, and low cost provide a new path for forming complex magnesium alloy components. However, since magnesium alloy is a heat-sensitive material, the continuous accumulation of heat during the arc additive manufacturing process will cause magnesium alloy to be prone to coarse columnar crystals and produce undesirable defects such as pores, which greatly affects the performance of the component. How to enhance the mechanical properties of magnesium alloy arc additive manufacturing components and improve anisotropy is a technical problem that needs to be solved urgently.

[0004] In order to improve the mechanical properties of magnesium alloys and improve casting defects, the structure and properties of the material can be adjusted by refining the grains, and the strength, toughness and plastic deformation ability of magnesium alloys can be improved. Among many refining methods, adding a refiner is the most practical and convenient method for refining magnesium alloy grains. Zr is one of the most effective grain refining elements for magnesium alloys. Adding Zr can greatly refine the grains of magnesium alloys while improving the strength and toughness of magnesium alloys. However, in Al-containing magnesium alloys, Zr will form a stable Al2O3 bond with Al. 3 Zr compounds, because they are body-centered cubic crystals, cannot be used as heterogeneous cores of magnesium alloys. Therefore, Zr cannot be directly added to Al-containing magnesium alloys. ZrO 2 As an important ceramic material, it has the characteristics of high strength, high wear resistance, high melting point, good chemical stability, etc. It has a good interface bonding with the magnesium alloy matrix and is an ideal reinforcing particle for preparing magnesium-based composite materials. 2 The particles are used as grain refiners for additively manufactured magnesium alloys, in order to improve the strength and toughness of the material by refining the grains of additively manufactured magnesium alloys. 2 Research on particles. Summary of the invention

[0005] The purpose of the present invention is to provide an interlayer coating nano ZrO 2 The invention discloses a method for grain refinement of magnesium alloy in additive manufacturing, which transforms columnar crystals in arc-added magnesium alloy into fine equiaxed crystals, so as to significantly improve the strength and elongation of the material.

[0006] To achieve the above object, the present invention provides the following technical solutions: A kind of interlayer coating nano ZrO 2 A method for particle refinement additive manufacturing of magnesium alloy grains, the method comprising: treating the surface of a substrate on a CMT arc additive manufacturing system, outputting a welding wire, depositing a layer of magnesium alloy on the surface of the substrate, and uniformly coating the surface of the deposited magnesium alloy with nano ZrO 2 The coating of the particles is deposited, and after a certain interlayer cooling time, the next layer of magnesium alloy is deposited, and the above process is repeated until the deposition is completed.

[0007] Preferably, the substrate and the welding wire are both made of AZ31 magnesium alloy.

[0008] Furthermore, the AZ31 magnesium alloy comprises the following components by mass percentage: aluminum Al: 2.5-3.5%, zinc Zn: 0.6-1.4%, manganese Mn: 0.2-1.0%, silicon Si: ≤0.08%, iron Fe: ≤0.003%, copper Cu: ≤0.01%, nickel Ni: ≤0.001%, and the balance is magnesium Mg.

[0009] Preferably, after each layer of magnesium alloy is deposited, a coating containing nano ZrO 2 Before the coating of the particles, a step of removing the surface oxide layer is included.

[0010] Furthermore, the step of removing the surface oxide layer includes grinding the surface with an angle grinder to remove the surface oxide layer.

[0011] Preferably, the process parameters of the CMT arc additive manufacturing system are: shielding gas flow rate 15-20L / min, welding speed 5-10mm / s, wire feeding speed 4-10m / min, welding current 85-120A, welding voltage 8-12V, dry extension 5-20mm, and then cooled to 20~100℃ and polished to remove impurities, and then a reciprocating additive manufacturing path is used to additively manufacture the next layer.

[0012] Furthermore, among the process parameters, the additive wire feeding speed is 9 m / min, the welding speed is 7 mm / s, the welding current is 115 A, the welding voltage is 11.9 V, and the dry extension length is 15 mm.

[0013] Preferably, the interlayer cooling time is 100-120s.

[0014] Preferably, the nano ZrO 2 The coating of the particles is an alcohol-based coating, in which ZrO 2 The mass fraction of the particles is 1-3%, ZrO 2 The average particle diameter is 50 nm.

[0015] Furthermore, the alcohol-based coating is ZrO 2 The particles and anhydrous ethanol are uniformly mixed by ultrasonic stirring. Compared with the prior art, the present invention has the following beneficial effects: 1. The preparation process of the present invention is simple, the preparation materials are relatively common, the price is low, the preparation time is short, and a lot of time and cost can be saved; 2. The present invention coats ZrO 2 The nanoparticles greatly refine the magnesium alloy grains, realize the transformation from columnar crystals to equiaxed crystals, and achieve a synergistic improvement in the material's strength and plasticity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A schematic diagram of a CMT arc additive manufacturing system used in the present invention; Figure 2 EBSD data diagram of the deposited component in the example of the present invention; Figure 3 Graph showing the tensile properties of a deposited component in an example of the present invention. DETAILED DESCRIPTION

[0017] The invention discloses an interlayer coating nano ZrO 2 The invention discloses a method for manufacturing magnesium alloy grains by particle refinement additive manufacturing, which belongs to the field of arc additive manufacturing. 2 The method of particle refinement additive manufacturing magnesium alloy grains is: nano ZrO 2 The particles were mixed with anhydrous ethanol to prepare nano ZrO 2 The mixed solution of particles is then vibrated by ultrasonic vibration to make the nano ZrO 2 The particles are evenly distributed in anhydrous ethanol. AZ31 welding wire with a diameter of 1.2 mm was selected, and the CMT process was used for additive deposition on the AZ31 substrate. The wire feeding speed was 9 m / min, the welding speed was 7 mm / s, the corresponding welding current was 115 A, and the welding voltage was 11.9 V. After each layer of magnesium alloy was deposited, the oxide layer was removed by an angle grinder, and the surface was evenly coated with ZrO 2 The mixed solution is deposited after a certain interlayer cooling time and then the next layer is deposited, and this process is repeated until the deposition is completed.

[0018] In an exemplary embodiment, the method of the present invention uses CMT to add material to form a magnesium alloy component. After depositing a layer of magnesium alloy, an angle grinder is used to remove the surface oxide layer, and a ZrO-containing coating is uniformly applied to the surface. 2 The mixed solution is deposited after a certain interlayer cooling time and then the next layer is deposited, and this process is repeated until the deposition is completed.

[0019] The welding wire and substrate used are both AZ31 magnesium alloy, and the composition by mass percentage is: aluminum Al: 2.5~3.5%, zinc Zn: 0.6~1.4%, manganese Mn: 0.2~1.0%, silicon Si: ≤0.08%, iron Fe: ≤0.003%, copper Cu: ≤0.01%, nickel Ni: ≤0.001%, and the balance is magnesium Mg. The diameter of the welding wire is 1.2mm.

[0020] The CMT additive process parameters are: shielding gas flow rate 15-20L / min, welding speed 5-10mm / s, wire feeding speed 4-10m / min, welding current 85-120A, welding voltage 8-12V, dry extension 5-20mm, and then cooled to 20~100℃ and polished to remove impurities, and then the reciprocating additive manufacturing path is used to additively manufacture the next layer.

[0021] The ZrO 2 The mixed solution is an alcohol-based coating, which is ZrO 2 The particles are mixed with anhydrous ethanol and uniformly stirred by ultrasonic. 2 The mass fraction of the particles is 1-3%, ZrO 2 The average particle diameter is 50 nm.

[0022] Preferably, the CMT additive wire feeding speed is 9m / min, the welding speed is 7mm / s, the corresponding welding current is 115A, and the welding voltage is 11.9V.

[0023] More preferably, the stem extension is 15 mm.

[0024] Further preferably, the interlayer cooling time is 100-120s.

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front end", "rear end", "two ends", "one end", "the other end" and the like indicating the orientation or positional relationship are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0027] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0028] The CMT-WAAM system used in the following embodiments is as follows: Figure 1 (a) shows the orientation and sampling position of the tensile sample. Figure 1 (b) As shown; the sample size for the tensile test is Figure 1 (c) shown.

[0029] Comparative Example The method for CMT additive manufacturing AZ31 comprises the following steps: Step 1: Before deposition, use an angle grinder to remove impurities on the substrate surface, clean the surface with anhydrous ethanol, and fix it on the working platform.

[0030] Step 2: Set the CMT process parameters, select the wire feeding speed of 9m / min, the welding speed of 7mm / s, the corresponding welding current of 115A, and the welding voltage of 11.9V. The shielding gas flow rate is 20L / min, the dry extension length is 15mm, and the interlayer cooling time is 100-120s. Use a reciprocating additive manufacturing path.

[0031] Step 3: According to Figure 1 As shown, the deposition process parameters described in step 2 are used, and a round-trip additive manufacturing path is used to repeatedly deposit until the additive component is deposited to obtain 0-ZrO 2 Sample (without ZrO 2 AZ31 sample of particles).

[0032] Step 4: According to Figure 1The cutting positions and sizes of the metallographic specimens and tensile specimens are shown. The required specimens are cut using an electric spark wire cutting machine. The metallographic specimens are extracted from the middle of the additive component, and the tensile specimens are extracted from a direction perpendicular to the substrate (deposition direction).

[0033] Step 5: After grinding and mechanically polishing the sample to remove surface scratches, the sample was observed by electron backscatter diffraction (EBSD). Figure 2 is the EBSD data of the deposited component, where (a1) is the IPF diagram, (a2) is the grain size statistics diagram, and (a3) ​​is the pole figure. Figure 2 As shown in (a1-a3), the microstructure of the deposited sample is mainly composed of vertically grown coarse columnar crystals with an average grain size of 190.5 μm and strong texture strength.

[0034] Step 6: Use a universal testing machine (Z050, Zwick Roell Testertechnik Test GmbH, Germany) to perform a room temperature tensile test, and set the tensile load loading speed to 0.6 mm / min. Figure 3 As shown, Figure 3 (a) Engineering tensile stress-strain curve showing the yield strength (YS) of the sample is 127 MPa. The UTS and EL of this study are compared with those of previously reported AZ31 series magnesium alloys prepared by WAAM and cast AZ31. Figure 3 (b) shows that its ultimate tensile strength (UTS) is 191 MPa and its elongation (EL) is 9.3%. Example

[0035] This embodiment adopts the ZrO 2 A method for reinforcing a magnesium-based composite material and additive manufacturing thereof comprises the following steps: Step 1: Before deposition, use an angle grinder to remove impurities on the substrate surface, clean the surface with anhydrous ethanol, and fix it on the work platform after drying.

[0036] Step 2: Set the CMT process parameters, select the wire feeding speed of 9m / min, the welding speed of 7mm / s, the corresponding welding current of 115A, and the welding voltage of 11.9V. The shielding gas flow rate is 20L / min, the dry extension length is 15mm, and the interlayer cooling time is 100-120s. Use a reciprocating additive manufacturing path.

[0037] Step 3: According to Figure 1 As shown, the deposition process parameters described in step 2 are used. After each layer of magnesium alloy is deposited, a ZrO layer containing 2 wt.% is uniformly coated on the surface of the layer. 2 Alcohol-based coating, and then deposit the next layer, using a round-trip additive manufacturing path, repeatedly depositing until the additive component is deposited, and 2-ZrO2 Sample (containing 2wt.% ZrO 2 AZ31 sample of particles).

[0038] Step 4: According to Figure 1 The cutting positions and sizes of the metallographic specimens and tensile specimens are shown. The required specimens are cut using an electric spark wire cutting machine. The metallographic specimens are extracted from the middle of the additive component, and the tensile specimens are extracted from a direction perpendicular to the substrate (deposition direction).

[0039] Step 5: After grinding and mechanical polishing the sample to remove surface scratches, the sample was ion etched for electron backscatter diffraction (EBSD) observation. Figure 2 is 2-ZrO 2 EBSD data of the deposited component, where (b1) is the IPF diagram, (b2) is the grain size statistics diagram, and (b3) is the pole figure. Figure 2 As shown in (b1-b3), 2-ZrO 2 The sample microstructure is mainly composed of equiaxed crystals with an average grain size of 62 μm. 2 The introduction of nanoparticles greatly refined the grain size of additively manufactured magnesium alloy specimens and achieved the transformation from columnar crystals to equiaxed crystals, while reducing the texture strength.

[0040] Step 6: Use a universal testing machine (Z050, Zwick Roell Testertechnik Test GmbH, Germany) to perform a room temperature tensile test, and set the tensile load loading speed to 0.6 mm / min. Figure 3 As shown, Figure 3 (a) Engineering tensile stress-strain curve showing 2-ZrO 2 The average YS of the samples is 104 MPa. The UTS and EL of this study are compared with those of the previously reported AZ31 series magnesium alloys prepared by WAAM and cast AZ31. Figure 3 (b) shows that its UTS is 213MPa and EL is 14.3%. 2 The introduction of nanoparticles increased the ultimate tensile strength (UTS) of the alloy sample by 11.5% and the elongation (EL) by 58%. The synergistic improvement of strength and plasticity was achieved. The enhancement of the mechanical properties of the sample can be attributed to the ZrO 2 Effect of nanoparticles on microstructural homogenization and grain refinement.

[0041] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

[0042] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified and replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for additive manufacturing of magnesium alloy grains by interlayer coating of nano ZrO2 particles, characterized in that: On the CMT arc additive manufacturing system, after the substrate surface is treated, the welding wire is output to deposit a layer of magnesium alloy on the substrate surface. A coating containing nano ZrO2 particles is evenly coated on the surface of the deposited magnesium alloy. After a certain interlayer cooling time, the next layer of magnesium alloy is deposited. The above process is repeated until the deposition is completed.

2. The method according to claim 1, characterized in that The substrate and welding wire are both made of AZ31 magnesium alloy.

3. The method according to claim 2, characterized in that The AZ31 magnesium alloy comprises the following components by mass percentage: aluminum Al: 2.5-3.5%, zinc Zn: 0.6-1.4%, manganese Mn: 0.2-1.0%, silicon Si: ≤0.08%, iron Fe: ≤0.003%, copper Cu: ≤0.01%, nickel Ni: ≤0.001%, and the balance is magnesium Mg.

4. The method according to claim 1, characterized in that After each layer of magnesium alloy is deposited, a step of removing the surface oxide layer is included before coating the coating containing nano ZrO2 particles.

5. The method according to claim 4, characterized in that The step of removing the surface oxide layer includes grinding the surface with an angle grinder to remove the surface oxide layer.

6. The method according to claim 1, characterized in that The process parameters of the CMT arc additive manufacturing system are: shielding gas flow rate 15-20L / min, welding speed 5-10mm / s, wire feeding speed 4-10m / min, welding current 85-120A, welding voltage 8-12V, dry extension 5-20mm, and then cooled to 20~100℃ and polished to remove impurities, and then a reciprocating additive manufacturing path is used to additively manufacture the next layer.

7. The method according to claim 6, characterized in that Among the process parameters, the additive wire feeding speed is 9 m / min, the welding speed is 7 mm / s, the welding current is 115 A, the welding voltage is 11.9 V, and the dry extension length is 15 mm.

8. The method according to claim 1, characterized in that The interlayer cooling time is 100-120s.

9. The method according to claim 1, characterized in that The coating containing nano ZrO2 particles is an alcohol-based coating, wherein the mass fraction of ZrO2 particles is 1-3%, and the average diameter of the ZrO2 particles is 50nm.

10. The method according to claim 9, characterized in that The alcohol-based coating is obtained by uniformly mixing ZrO2 particles and anhydrous ethanol through ultrasonic stirring.